Conflict Management In Event Performance Teams - Malik, Anjali (International Journal of Psychosocial Rehabilitation, 2019)
The term "conflict" tends to bring forth negative feelings in and of itself. It reminds us of shouting matches and possible emotional harm. However, disagreement may boost team effectiveness if it is utilised deliberately and managed well. The capacity to have healthy disagreements is crucial to the growth of high-performing teams. When people’s worldviews intersect, conflict is inevitable. Although this may very well turn out badly, there are a few of important instances in which disagreement really helps teams succeed